Boatwomen Training Scheme, 1942-1945
1945 1939-1945 "Boatwomen Training Scheme, 1942-1945" [HFR0238b], 1942-1945 In 1941, Frances Marian 'Molly' Traill approached the Ministry of War Transport with a scheme to train women boat crews to help the country with its shortage of manpower on the canals. The Ministry was impressed and persuaded the Grand Union Canal Carrying Company to pioneer the scheme. Molly Traill and Eily Gayford were recruited as trainers when the scheme launched in February 1942. The scheme was later extended to other canals such as the Leeds and Liverpool.